Spectral Analysis for Detecting Affective Variations in Arabic Speech - Tria Barkahoum (Pegem Journal of Education and Instruction, 2025)
This study aims to explore the effectiveness of spectral audio analysis techniques for detecting emotionalvariations in spoken Arabic discourse. With the rapid advancement of human–machine interactions,understanding a speaker's emotional state has become a fundamental component of developing more intelligent and responsive systems.